Influence of eWOM and Brand Image on Purchase Decisions of Luxcrime Cosmetic Products in Bandar Lampung - Safitri, Andela; Sari, Aida (PT. Riset Press International, 2025)
The growth of internet technology continues to increase, accompanied by the increasing population of Indonesia's young population, which encourages public awareness of the importance of maintaining appearance and skin health. The internet makes it easy for consumers to find information, reviews, and product images before buying Luxcrime cosmetic products. This allows companies to pay attention to the influence of electronic word of mouth and brand image on purchasing decisions for Luxcrime cosmetics. This study aims to determine the effect of electronic word of mouth and brand image on purchasing decisions for Luxcrime cosmetic products in Bandar Lampung. This study used a quantitative approach and a questionnaire to sample 110 respondents influenced by electronic word of mouth and brand image when purchasing Luxcrime cosmetics in Bandar Lampung. The results of data analysis using multiple linear regression show that positively and significantly, the electronic word of mouth variable and the brand image variable affect the decision to buy Luxcrime cosmetic products in Bandar Lampung.